Estudo numérico e experimental da geração de golfadas em um escoamento bifásico de gás-líquido - Conte, Marco Germano (2014)
Many industrial processes like crude oil transportation in pipelines operate on two-phase flow regime, especially in slug flow pattern. Slug flows are characterized by the intermittent succession of liquid slugs having a large momentum, followed by long bubbles of compressible gas. This kind of flow has been a topic of research over the last decades; however, few mathematical models for this complex flow can be found in the literature. Among those, one might mention the Eulerian two-fluid and drift flux, and the Lagrangian slug-tracking. Based on the work of Renault (2007), this work presents a Lagrangian methodology to capture the process of slug initiation for horizontal and near horizontal pipes. Starting from one dimensional two-fluid model, the equations of momentum and mass conservation were simplified. The motion generated by the dynamic pressure of the gas was decoupled from the slow movement of the liquid film. The resulting system of equations for the gas phase was discretized using the finite difference method and solved with the tri-diagonal matrix algorithm (TDMA). The liquid motion in the bubbles was then modeled by a modified version of shallow water equations. A software using Intel Visual Fortran language to simulate the process of slug initiation in a gas-liquid stratified flow was developed. Wave growth in the liquid-gas interface was numerically monitored until one of those waves reached the top of the pipe to form a slug. Numerical simulations were performed for different gas-liquid flow conditions, in order to evaluate the ability of the model to generate slugs. Experimental data to validate the code were gathered at the experimental facility of NUEM/UTFPR. The data were acquired using two-wire resistive sensors. The numerical results showed to be strongly dependent on mesh size. Because of this, a limiting criterion for the mesh size was developed. The linear analysis showed higher wave growth rate to this model than the two-fluid model. The results showed consistency when compared to the experimental data, especially in the neighborhoods of the region where the model is ill-posed.